Peningkatan Soft Skill Mahasiswa FEBI IAIN Lhokseumawe Melaui Microsoft Office Practice - Ainun Mardhiah; Nur Azizah; Basrul Basrul (Malik Al-Shalih : Jurnal Pengabdian Masyarakat, 2023)
The primary goal of this community engagement project was to distribute knowledge concerning soft skills in the field of computer science, with a specific focus on the practical implementation of Microsoft Office. The intention was to enhance students' abilities and equip them for proficient performance in professional settings. This endeavor was executed through a sequence of phases, which included the collection of student data, examination of educators' and classroom prerequisites, conceptualization, composition, and implementation of training sessions, all of which were complemented by comprehensive documentation. Throughout the training sessions, students received initial guidance before embarking on practical exercises that utilized Microsoft Office tools, encompassing Microsoft Word, Microsoft Excel, and Microsoft PowerPoint. During the training process, students actively participated in hands-on exercises to directly apply the skills they had acquired. The desired outcomes of this initiative were aimed at enhancing students' competence in effectively using and advancing their proficiency with Microsoft Office applications. As a result, this process optimized tasks such as document drafting, thesis presentations, data manipulation, and the creation of various documents like correspondence reports, resulting in heightened precision and workflow efficiency